EFFECTIVENESS OF COMPLEMENTARY TREATMENTS IN DIABETIC WOUND HEALING - dwi prasetio, ossi; Suciati; Arief Hidayat, Shulhan; Audilla, Amita (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Diabetic foot ulcers are typical wounds that are serious and common complications in people with diabetes with a long healing time. The cost of treating diabetic foot ulcers is relatively expensive because the price of modern dressings is less affordable and the recovery time is long. Complementary dressing interventions are expected to heal diabetic foot ulcers effectively. This case study aims to analyze the results of the implementation of wound care with complementary dressings on the healing of diabetic foot ulcers. This case study uses a descriptive method with a nursing care process approach. The subjects of the case study were patients with diabetes mellitus with grade 1-2 diabetic ulcers. The subjects of the case study were 2 people, who were obtained randomly. The subjects of the case study had signed an informed consent before data collection. The population used was all patients with diabetic foot ulcers. The number of samples used was 2 female patients. The data collection tool used the Bates-Jensen Wound Assessment Tool (BWAT) assessment sheet. The results obtained were an improvement in the wound as indicated by an increase in the score on the assessment sheet with an average difference of 3 points. The complementary dressing technique accelerates the healing of diabetic wounds